Evaluation of the Equality Education Program at LPKA Class II Jakarta - Eka Rista Harimurti; Rugaiyah Rugaiyah; Budi Santoso (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This research aims to see the effectiveness of implementing equality education programs at the Jakarta Class II Special Child Development Institute (LPKA) in terms of the context, input, process and product of the equality education program. This research is descriptive qualitative research using evaluation research methods with the CIPP (Context, Input, Process, Product) evaluation model in the implementation of equality education programs at LPKA Class II Jakarta. Data collection was carried out through observation, interviews and documentation which was then processed using data reduction techniques, data presentation and conclusions. Based on the results of data analysis, it is known that the implementation of equality education at LPKA Class II Jakarta has been running well and is in accordance with the standards for implementing equality education for Package A, Package B and Package C programs, Directorate of Community Guidance and Child Eradication, Directorate General of Corrections, Ministry of Law and Human Rights, Republic of Indonesia. Indonesia.